EVALUASI IMPLEMENTASI PROGRAM KEAGAMAAN (MAN-PK) MADRASAH ALIYAH NEGERI 2 SAMARINDA MENGGUNAKAN MODEL CIPP - M. Isro' Zainuddin; Zurqoni; Sugeng (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the implementation of the Religious Program at Madrasah Aliyah Negeri Program Keagamaan (MAN-PK) MAN 2 Samarinda using the CIPP (Context, Input, Process, Product) evaluation model. The study employed a descriptive qualitative approach with an evaluative research design. Research participants included the MAN-PK program coordinator, religious education teachers, and MAN-PK students, selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, and analyzed using thematic coding techniques through stages of data reduction, data display, and conclusion drawing, resembling qualitative analysis with NVivo software. Data credibility was ensured through source and technique triangulation. The findings indicate that the context aspect reflects clearly formulated program objectives aligned with the policies of the Ministry of Religious Affairs and well understood by all stakeholders. The input aspect shows that teacher competence and student selection systems are adequate, although supporting facilities still require improvement. The process aspect reveals that the implementation of religious learning activities such as kitab studies, Qur’anic memorization, Arabic language development, and habituation of worship practices is structured and intensive, yet faces challenges related to students’ workload management. The product aspect demonstrates positive outcomes in enhancing students’ religious competence, discipline, and religious character development. Overall, the implementation of the MAN-PK Religious Program at MAN 2 Samarinda is categorized as good. Strengthening supporting facilities and optimizing program management are recommended to ensure program sustainability and continuous quality improvement.